(untitled) (UKLO Proceedings, 2026)
In North Macedonia, Non-Governmental Organizations (NGOs) play an important role by addressing specific Sustainable Development Goals (SDGs) themes that prioritize human security. This study aims to answer the research question: How engaged are NGOs in North Macedonia in fulfilling the SDGs that touch on human security themes? The hypothesis is that NGOs in North Macedonia are moderately engaged in achieving the SDGs due to limited information and financial opportunities.The methodology used in our scientific paper is based on a qualitative analysis of United Nations reports on the SDGs in North Macedonia, the Government of North Macedonia’s strategic documents, and NGOs’ reports on their engagement with the SDGs.Some NGOs in North Macedonia are engaged in achieving the SDGs, with a special emphasis on human security. It is expected that further analysis will establish that NGOs play an important role in human security, as they operate at the local level and can more easily foster regional cooperation that advances the SDGs with a human security character.NGOs in North Macedonia are an important factor in connecting sustainable development and human security by engaging in work aligned with the SDGs across various themes. Their efforts to fulfill the SDGs with a human security character are constrained by the limited support they receive from institutions and donors. Strengthening capacities, creating new opportunities, and providing greater institutional and financial support are essential to their commitment to fulfilling the SDGs.